A rare case of appendiceal adenocarcinoma mimicking urinary tract symptoms - Shamsuddin Perisamy, Rajeev; Tharek, Anas (Elsevier Inc., 2025)
Primary appendiceal carcinoma is a rare malignancy that presents with a spectrum of clinical symptoms, primarily gastrointestinal in nature. Rarely, it invades the urinary bladder, leading to urinary tract symptoms. We report a case of a 63-year-old female with a 1-year history of hematuria and recurrent urinary tract infections (UTIs) initially treated as simple UTIs. Further investigations, prompted by the failure of medical treatment and symptom recurrence, revealed appendiceal adenocarcinoma invading the urinary bladder. This case highlights the potential for appendiceal malignancy to masquerade as urinary symptoms and underscores the importance of thorough investigation in cases of recurrent urinary tract symptoms, particularly when conventional treatment fails.